Síntese e cristaloquímica de complexos de mercúrio(ii) com o ligante 1-(3-trifluorometilfenil)-3-(3-nitrofenil)triazeno - Crespan, Estela dos Reis (2005)
This work shows the crystaline/molecular structure of two mercury(II) complexes with a same monocateneted triazene ligand previolsly deprotonated. The reaction between mercury(II) acetate, 1-(3-nitrophenyl)-3-(3-trifluorometilphenyl)triazene and triphenylphosphine in a methanol of yields the complex [Hg(CF3C6H4NNNC6H4NO2)2(C18H15P)] (1). (1) cristallizes in triclinic system, space group P 1, Z = 2, with cell parameters a = 11.8334(3) Å, b = 13.7747(3) Å, c = 15.3909(4) Å, α = 75.9550(10)°, β = 70.8900(10)°, γ = 65.9750(10)°. The refinament of this estructure converges to the follow discordance indexes R1 = 0.0525 e wR2 = 0.1342. The coordination sphere of mercury(II) ion is formed by two deprotonated triazenido ligands and a triphenilphosphine molecule imposing a trigonal-distorted coordination geometry to the metallic center. Intermolecular interactions of C-H···O type are observed in this structure originating chains of molecules guided parallel to the crystallographic direction [101]. These chains for your time settle of form centrosimetric some relative ones to the other ones, forming bidimensional supramolecular arrangement binding intermolecular interactions type C-H···F. The reaction between mercury(II) acetate, 1-(3-nitrophenyl)-3-(3- trifluorometilphenyl)triazene and pirydine in a methanol of yields the complex [Hg(CF3C6H4NNNC6H4NO2)2(C5H5N)] (2). (2) cristallizes in monoclinic system, space group P21/c, Z = 4, with cell parameters a = 13,5586(3) Å, b = 19,2937(5) Å, c = 12,9152(3) Å, β = 90,9610(10)°. The refinement of this structure converged to the discordance indexes R1 = 0,0470 and wR2 = 0,1365. The coordination sphere of mercury(II) ion is formed by two deprotonated triazenido ligands and a pyridine molecule imposing a T-distorted coordination geometry to the metallic center. The molecular structure reveals disordered fluorine and oxygen atoms related to the the trifluoromethyl and nitro substituents, respectively. A discussion of intermolecular interactions via C-H···O and C-H···F is not possible at this stage of the structure analysis. On the other hand, the crystal structure of (2) in contrast to other examples of this class of compounds, does not present intermolecular metal-arene π interactions between the Hg(II) ion and terminal aryl substituents of the triazenide ligand. Beside the X-ray structure analysis, both the complexes (1) and (2) were also characterized by melting point determination and infrared spectroscopy.